Hahn’s functions and Baire classifications (in Ukrainian) - H. A. Hlushko; V. K. Maslyuchenko (Математичні Студії)
Hahn’s results about Baire classifications the real values separately continuous functions are moved on the functions with values in arbitrary local convex spaces.